Student Authentication in eAssessments Using Online Proctored Exam System: Accounting Educator Views in Fiji - Roy, Sandhiya (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
With the advancement in eLearning technologies, eAssessments are becoming widely used. The overarching challenge in eAssessment is student authentication. An online invigilated or remote proctored exam system that engages a human proctor, supervising live via webcam, is a widely accepted method for student authentication. This study obtained views of tertiary accounting academics in Fiji using semi-structured interviews. Though educators prefer online assessments, there is a strong consensus that student authentication is a challenge. The findings reveal that academics are willing to accept online proctored exam system because it has the capability to validate students, along with minimising other forms of academic misconduct during exams. According to the academics, the online proctored exam system may be more acceptable among the postgraduate students compared to the undergraduate students because of the digital resource issues. It is also essential that attention is paid to network connectivity issues in Fiji when implementing online proctored exam systems.